2011
DOI: 10.1007/s11199-011-0048-8
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sample Characteristics and Experience with Infidelity on Romantic Jealousy

Abstract: Past research has suggested that men are more upset by imagined sexual than emotional infidelity, and women are more upset by imagined emotional infidelity than sexual infidelity. However, experience with infidelity, methodology, and age and gender of the sample may help to explain inconsistent results. Two hundred ninety-four English-speaking undergraduate students and 325 noncollege adults in a large mid-Atlantic urban area of the U. S. completed forced-choice or continuous-scale anonymous questionnaires reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 43 publications
(98 reference statements)
1
11
0
4
Order By: Relevance
“…Further, the experience of personal infidelity or a partner's infidelity may also influence infidelity imagination; in other words, whether or not individuals had experienced partner infidelity affected their responses regarding their partner's infidelity (e.g. Harris, 2003b;Tagler, 2010;Varga, Gee, & Munro, 2011). The experience rates of partner infidelity in Western cultures are generally higher than in Asian cultures.…”
Section: Imagination Hypothesismentioning
confidence: 99%
“…Further, the experience of personal infidelity or a partner's infidelity may also influence infidelity imagination; in other words, whether or not individuals had experienced partner infidelity affected their responses regarding their partner's infidelity (e.g. Harris, 2003b;Tagler, 2010;Varga, Gee, & Munro, 2011). The experience rates of partner infidelity in Western cultures are generally higher than in Asian cultures.…”
Section: Imagination Hypothesismentioning
confidence: 99%
“…Women and men may also vary in their emotional responses to perceived partner ESI; men tend to report a greater degree of jealousy and distress in response to partner infidelity and to be more threatened by sexual rather than emotional infidelity of their female partners, whereas women report more distress in response to emotional infidelity of their male partners (Edlund, Heider, Scherer, Farc, & Sagarin, 2006; Frederick & Fales, 2016; Harris & Christenfeld, 1996). However, some research has demonstrated that age and prior experiences with partner ESI moderate these findings (Varga, Gee, & Munro, 2011), and that gender discrepancies in general may be decreasing in younger cohorts (Atkins, Baucom, & Jacobson, 2001; Fincham & May, 2017; Mark et al, 2011). Thus, age may be another key factor in understanding risk for infidelity.…”
mentioning
confidence: 99%
“…Они рассматривались в рамках дискус-сии между сторонниками эволюцион-ной теории и социально-когнитивной теории Varga, Gee, Munro, 2011;Ward, Voracek, 2004;. В данной дискуссии о половых различиях в восприятии двух видов не-верности эти теории выглядят противо-положными, однако те же теории могут рассматриваться и как взаимодополняю-щие .…”
Section: национальный психологический журнал № 2(22) 2016unclassified
“…Эти различные ре-акции основаны не только на различ-ной роли партнеров в репродуктивном процессе, но и на процессах атрибу-ции чувств и действий каждого, которые, в свою очередь, зависят от социальных норм, образцов и ожиданий. Кроме того некоторые половые различия романти-ческой ревности могут быть объяснены возрастными особенностями и разным опытом реальной неверности (Varga, Gee, Munro, 2011).…”
Section: национальный психологический журнал № 2(22) 2016unclassified